(untitled) (FAVE Sección Ciencias Veterinarias, 2022)
The aim of this work was to evaluate the effects of the stocking density, shed area and its interaction, on final body weight and uniformity in male and female chickens reared in mixed flocks, in winter. Commercial hybrid chickens were housed in two darkened houses divided transversely into three zones: Extractors, Intermediate and Panels. Two densities were tested: standard (14 chickens / m2) and reduced (12 chickens / m2). In each zone six sampling points were defined where at 41 days of age 10 males and 10 females were weighed individually and the coefficient of variation of weight was calculated. Density x zone interaction for body weight was significant (p = 0.002) in males but not in females (p = 0.933) in which, regardless of the shed area (p = 0.190), higher weight was observed with reduced density (p < 0.0001). For the coefficient of variation, in males, there was no significant effect of the interaction (p = 0.151) or shed area (p = 0.137) and a significant one for density (p = 0.026) with the lowest coefficient of variation observed with reduced density. In females none of the effects were significant (Density: p = 0.864; Zone: p = 0.122; Interaction: p = 0.453).